Legislative power in emerging African democracies - Barkan, Joel D. (Lynne Rienner Publishers, 2009)
A study of legislative development in Africa which explores why variations in the extent of legislative authority and performance across the continent are only partially related, if at all, to the overall level of democratization. Constraints that have retarded the development and power of legislatures across Africa, and how members of some legislatures are breaking free of those constraints, are analyzed. The impact of the legislative branch on the political process in six emerging African democracies is reviewed.